2018
DOI: 10.1038/s41386-017-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

The OPRM1 A118G polymorphism: converging evidence against associations with alcohol sensitivity and consumption

Abstract: The endogenous opioid system may be involved in the development and maintenance of alcohol use disorder (AUD) and is a target for existing AUD pharmacotherapies. A functional polymorphism of the mu-opioid receptor gene (OPRM1 A118G, rs1799971) may alter the risk of developing AUD. Human laboratory studies have demonstrated that minor allele carriers self-administer more alcohol, show greater sensitivity to alcohol's effects, and exhibit increased alcohol-induced dopamine release. On the other hand, large genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
0
19
1
Order By: Relevance
“…Further supporting this idea, data suggest that alcohol infusion behaviors correspond with “real‐world” behavioral and clinical phenomena of interest, similar to how alcohol ingestion behaviors correspond with these outcomes. Response to the alcohol clamp has demonstrated sensitivity to family history of alcoholism (Blekher et al, 2002; Kareken et al, 2010a; Morzorati et al, 2002; Ramchandani et al, 1999b; albeit, like the oral literature, inconsistently), drinking history (Kerfoot et al, 2013), neurophysiology (Gilman et al, 2012a; Kareken et al, 2010b, 2012; Oberlin et al, 2015; Strang et al, 2015; Yoder et al, 2009, 2016), pharmacologic targets or interventions (Gowin et al, 2016; Leggio et al, 2013; Ralevski et al, 2017; Spagnolo et al, 2014), metabolism (Marshall et al, 2014; Neumark et al, 2004; Ramchandani et al, 2001), and interactions with known risk genotypes (Kosobud et al, 2015; Roh et al, 2011; Sloan et al, 2018) and personality traits (Hendershot et al, 2015; Leeman et al, 2014; Plawecki et al, 2018c). Other alcohol infusion challenge designs have also corresponded with neurophysiology (Oberlin et al, 2018) and drinking history (Wetherill et al, 2012).…”
Section: Issues To Consider In Choosing Route Of Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Further supporting this idea, data suggest that alcohol infusion behaviors correspond with “real‐world” behavioral and clinical phenomena of interest, similar to how alcohol ingestion behaviors correspond with these outcomes. Response to the alcohol clamp has demonstrated sensitivity to family history of alcoholism (Blekher et al, 2002; Kareken et al, 2010a; Morzorati et al, 2002; Ramchandani et al, 1999b; albeit, like the oral literature, inconsistently), drinking history (Kerfoot et al, 2013), neurophysiology (Gilman et al, 2012a; Kareken et al, 2010b, 2012; Oberlin et al, 2015; Strang et al, 2015; Yoder et al, 2009, 2016), pharmacologic targets or interventions (Gowin et al, 2016; Leggio et al, 2013; Ralevski et al, 2017; Spagnolo et al, 2014), metabolism (Marshall et al, 2014; Neumark et al, 2004; Ramchandani et al, 2001), and interactions with known risk genotypes (Kosobud et al, 2015; Roh et al, 2011; Sloan et al, 2018) and personality traits (Hendershot et al, 2015; Leeman et al, 2014; Plawecki et al, 2018c). Other alcohol infusion challenge designs have also corresponded with neurophysiology (Oberlin et al, 2018) and drinking history (Wetherill et al, 2012).…”
Section: Issues To Consider In Choosing Route Of Administrationmentioning
confidence: 99%
“…The literature associating intravenous alcohol self‐administration paradigms with behavioral and clinical phenotypes is emerging. Intravenous alcohol self‐administration has been associated with family history of alcoholism (Zimmermann et al, 2009), drinking history (Bujarski et al, 2018; Stangl et al, 2017), including binge drinking (Sloan et al, 2019), AUD risk (Gowin et al, 2017), craving (Green et al, 2019; Wardell et al, 2015), personality traits (Stangl et al, 2017; VanderVeen et al, 2016), sex differences (Cyders et al, 2016; Plawecki et al, 2018b), pharmacologic targets or interventions (Suchankova et al, 2017), and risk genotypes (Hendershot et al, 2016, 2017; Plawecki et al, 2013; Sloan et al, 2018; Suchankova et al, 2017).…”
Section: Issues To Consider In Choosing Route Of Administrationmentioning
confidence: 99%
“…Intravenous self‐administration also eliminates cues such as smell, taste, and appearance, so consumption should be primarily driven by the pharmacodynamic effects of alcohol, such as dopamine release in the nucleus accumbens . This paradigm has been used to test the effects of medications on self‐administration, to show that males consume more than females, and to examine genetic effects on alcohol consumption and sensitivity . There is evidence that phenotypes elucidated in the laboratory have important clinical implications.…”
Section: Introductionmentioning
confidence: 99%
“…The A118G SNP is associated with an altered response to drugs of abuse; however, some studies have reported divergent ef- fects (Ray and Hutchison, 2004;Ehlers et al, 2008;Miranda et al, 2010;Koller et al, 2012;Enoch, 2013;Sloan et al, 2018). Significant behavioral differences between the two genotypes have been reported in two mouse models of the A118G SNP: that is, the A112G knock-in and "humanized" A118G mouse models (Mague et al, 2009;Bilbao et al, 2015;Browne et al, 2017).…”
Section: Behavioral Alterations In Rodent Models Of Oprm1 A118g Snpsmentioning
confidence: 99%
“…However, the results are inconsistent, which may be explained by variations in the genetic backgrounds between different ethnic groups (Ray and Hutchison, 2004;Ehlers et al, 2008;Miranda et al, 2010;Koller et al, 2012;Enoch, 2013). A more recent epidemiological study, using a large subject pool, also argued against the link between A118G and alcohol use (Sloan et al, 2018). However, in these clinical studies, a host of potential covariates of addiction severity makes it impossible to isolate the effects of this genotype alone.…”
Section: Introductionmentioning
confidence: 99%